Enhanced bioremediation of petroleum contaminated soils using an engineered bioreactor design CFB Petawawa, Petawawa, Ontario. - McNicoll, Dan. (University of Ottawa (Canada), 1994)
An engineered bioreactor system was designed and constructed to bioremediate approximately 1,800 m$\sp3$ of petroleum-contaminated soil at CFB Petawawa, Petawawa, Ontario. The bioremediation facility operated between May-November 1993. The facility consists of four above ground bioreactors each incorporating aeration piping and a water/nutrient delivery system. The aeration piping is connected to a central vacuum pump which draws air through the bioreactor leachate collection system enables the leachate to be amended. The bioreactors are covered with an opaque vapour barrier. Monitoring involved the collection of soil, water and air samples on a weekly and bi-weekly basis and various field measurements. A detailed microbial monitoring program was also implemented. Total petroleum hydrocarbon concentrations in the bioreactor soils were found to have been reduced by 97%. Temperature had an effect on the rate of petroleum biodegradation. Little or no evidence suggested that the continuous addition of nutrients to the soil had a significant effect on the rate of biodegradation. The estimated treatment cost for this project was 70-$90 per tonne. This facility however, is reusable and hence the potential exists to lower the net treatment cost to 20--\$40 per tonne. This project has shown that diesel contaminated soil can be efficiently and effectively treated to meet the most stringent federal and/or provincial criteria in a cost effective manner over a typical Canadian summer. (Abstract shortened by UMI.)
Keywords: Environmental Sciences.